The Impact of the Global Economic Crisis on Support for Democracy - Hans-Dieter Klingemann; Ursula Hoffmann-Lange (Historical Social Research, 2018)
This contribution provides a brief introduction into the second part of this HSR Special Issue. It informs about an ongoing project on the development of democracy in seven countries, five 'new' and two 'established' democracies. The five new democracies are Chile, South Korea, Poland, South Africa and Turkey. They are compared to Sweden and Germany. The five new democracies are located in different world regions and have different cultural and historical backgrounds. The contribution provides basic economic and political information on these countries. It also describes the common data base used by the six contributions: two surveys of members of parliament conducted in 2007 and 2013 as well as waves 5 and 6 of the World Values Survey conducted at about the same time. The common focus of all six contributions is the analysis of change in political legitimacy between 2007 and 2013.
Keywords: 330; parliamentarians; citizens; quality of democracy; support for democracy